1974
DOI: 10.1172/jci107824
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Circulating Vasoactive Substances in Hemorrhagic Shock and Their Pharmacologic Manipulation

Abstract: A B S T R A C T (a)Hemorrhage(b) Plasma catecholamines (CA) steadily increased during hemorrhage and peaked during compensation (a 100-fold increase). The CA decreased progressively during decompensation.(c) Prostaglandin (PG) E-like material was observed in arterial blood for 15-60 min (after hemorrhage); the peak arterial concentration was 2.6 ng/ml blood. Indomethacin (i.v., before 80% of maximum bleedout): (i) confirmed the presence of PGE, (ii) increased blood pressure, and (iii) increased blood loss.(d) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…As would be expected, they have a role in the maintenance of blood pressure, especially in haemorrhagic states [52]. The circulating concentrations of adrenaline, vasopressin and angiotensin II also increase in other conditions (e.g., starvation, hypoglycaemia, Na' depletion) to levels which will affect the liver (see discussion in ref.…”
Section: Functional Significance Of Catabolic Hormone Effects On the mentioning
confidence: 78%
“…As would be expected, they have a role in the maintenance of blood pressure, especially in haemorrhagic states [52]. The circulating concentrations of adrenaline, vasopressin and angiotensin II also increase in other conditions (e.g., starvation, hypoglycaemia, Na' depletion) to levels which will affect the liver (see discussion in ref.…”
Section: Functional Significance Of Catabolic Hormone Effects On the mentioning
confidence: 78%
“…The enhancement ofthe activity ofthe renin-angiotensin system during hemorrhage is a well-accepted phenomena (18)(19)(20) that has stimulated physiologic investigation for a number of years. Studies in the nonfiltering kidney suggest that hemorrhage may provide a multifactorial stimulus for renin release (9 Although Romero et al (11) found that inhibition of prostaglandin synthesis abolished the renin response to hemorrhage in the conscious rabbit, this was not found to be the case in the present study in the anesthetized dog.…”
Section: Discussionmentioning
confidence: 99%
“…However, hepatic glycogen content in the SHRs receiving enflurane was significantly lower than that in those receiving pentobarbital, and both myocardial and hepatic L/P ratios in the SHRs receiving enflurane were significantly higher than those receiving none. It is well established that circulating cathecolamines are raised during hemorrhage and this increases glycogenolysis and hyperglycemia (Jakschick et al 1974). It is also stated that the elevation in L/P ratio frequently observed in the shock state reflects decreased cell phosphorylation rather than the cell hypoxia (Yoshitake et al 1983).…”
Section: Discussionmentioning
confidence: 99%